ANALISIS YURIDIS TERHADAP DUGAAN PELANGGARAN HAK ASASI MANUSIA BERAT OLEH ABRI DALAM PERISTIWA KERUSUHAN JAKARTA TAHUN 1998 - Nur Ahmad; Nasution, Aulia Rosa (The Juris, 2025)
The Jakarta riots of May 1998 marked one of the darkest episodes in Indonesia's contemporary history, characterized by widespread violence, looting, arson, sexual assaults, and targeted attacks against ethnic Chinese communities. Amidst the political upheaval that led to the fall of the New Order regime, allegations emerged regarding the involvement or negligence of the Indonesian Armed Forces (ABRI) in these human rights violations. Despite numerous reports and investigations, including by the National Human Rights Commission (Komnas HAM), legal proceedings remain stagnant. This study aims to conduct a juridical analysis of the alleged gross human rights violations committed by ABRI during the 1998 Jakarta riots, based on national legal instruments—particularly Law No. 26 of 2000 on Human Rights Courts—and international human rights norms. The research employs a normative juridical approach combined with transitional justice theory, emphasizing truth-seeking, justice, reparations, and institutional reform. By examining the legal responsibilities of state actors and the structural impediments to prosecution, this study identifies key legal and political gaps that have hindered the realization of justice. The findings underscore the absence of institutional accountability and the inadequacy of legal mechanisms in addressing past atrocities. This research contributes to the discourse on transitional justice in Indonesia and offers recommendations for strengthening legal frameworks to ensure state accountability and prevent future violations.